Experimental and numerical investigation of hot-rolled stainless steel equal leg angles under compression. (June 2020) - Sarquis, F.R.; de Lima, L.R.O.; da S Vellasco, P.C.G.; Rodrigues, M.C.
Abstract: An experimental and numerical study was conducted aiming to understand the flexural-torsional buckling phenomenon in angle fixed end columns with equal compact legs made of hot rolled austenitic stainless steel 304. The experimental programme was divided into four steps: cross-sections and column length selection; measurement of the columns initial geometric imperfections, i.e., local (cross-section rotation) and global (major and minor-axis bending); material characterisation in terms of its response under compression and tension stresses; development of the tests aiming to determine: failure modes, equilibrium paths and the columns' ultimate loads. A numerical investigation was also carried out, where the finite element models were validated against the performed experiments, to expand the experimental results to cover additional cross-sections and column lengths. This was followed by an assessment of two design methods for angle fixed ends columns with compact equal legs: Eurocode 3 – part 1.4, specific for the stainless steel materials, and a design procedure based on the direct strength method developed by Dinis et al. for carbon steel materials. These two methods proved not to be reliable for the column ultimate loads prediction and motivated the development of two novel design procedures based on the Eurocode 3 – part 1.4 methodology. These two novel design methods provided more consistent results when the flexural-torsional buckling ultimate limit state controls the structural design of austenitic stainless steel equal leg angle.